Comparison of wireless sensor network and radio frequency identification for the process control of distributed industrial systems - Abrishambaf, Reza; Akbari, Aliakbar; Hashemipour, Majid (Sage Publications Ltd, 2014)
In today's demanding market, flexibility and reconfigurability play an important role in manufacturing industries. This can be achieved by employing distributed control system such as International Electrotechnical Committee 61499 function block, which is a new standard adopted for industrial-process measurement and control system. On the other hand, wireless systems have been adopted recently in manufacturing systems as a replacement for conventional wired systems. This includes the wireless sensor network and radio frequency identification, which are emerging technologies adopted recently in a wide range of applications, especially in industry sectors. This article presents and compares the application of wireless sensor network and radio frequency identification in the process control of industrial system on the basis of International Electrotechnical Committee 61499 standard. Two process control architectures are considered for a case of an assembly line in order to compare and measure performance by employing Petri net as a mathematical modelling tool.
Keywords: Distributed control systems; International Electrotechnical Committee 61499 function blocks; radio frequency identification; wireless sensor networks